2002
DOI: 10.1177/0091270002042001007
|View full text |Cite
|
Sign up to set email alerts
|

Cyclobenzaprine Pharmacokinetics, Including the Effects of Age, Gender, and Hepatic Insufficiency

Abstract: The pharmacokinetics and bioavailability of cyclobenzaprine, a widely used muscle relaxant, were investigated in four clinical studies, and the effects of age, gender, and hepatic insufficiency were characterized. Cyclobenzaprine plasma clearance was 689 ml/min, and the bioavailability of a 5 mg oral dose was 0.55. Following oral doses of 2.5 to 10 mg tid in healthy young subjects, cyclobenzaprine pharmacokinetics were linear, and plasma concentrations generally increased proportional to dose. There was about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 11 publications
3
36
0
1
Order By: Relevance
“…The close temporal association strongly suggests that the dystonic symptoms were caused by cyclobenzaprine. The effective half-life of cyclobenzaprine is 18 h [10] , and after 4 days steady state is reached which equals the period of time during which cyclobenzaprine had been given.…”
Section: Discussionmentioning
confidence: 99%
“…The close temporal association strongly suggests that the dystonic symptoms were caused by cyclobenzaprine. The effective half-life of cyclobenzaprine is 18 h [10] , and after 4 days steady state is reached which equals the period of time during which cyclobenzaprine had been given.…”
Section: Discussionmentioning
confidence: 99%
“…After 10 mg immediate-release tablet oral administration, cyclobenzaprine is absorbed with estimates of mean bioavailability ranging from 33% to 55% [911]. Approximately 93% of the drug is bound to plasma proteins [12].…”
Section: Introductionmentioning
confidence: 99%
“…Cyclobenzaprine hydrochloride is a centrally acting muscle relaxant that has been widely used over the past 30 years for relief of muscle spasm associated with acute, painful musculoskeletal conditions (Borenstein et al, 2003;Browning et al, 2001; Katz et al, 1988;Winchell et al, 2002). Disposition studies in humans and laboratory animals have previously shown that cyclobenzaprine hydrochloride is well absorbed (Hucker et al, 1978), is widely distributed among body tissues (Hucker et al, 1978), is subject to enterohepatic circulation (Wang et al, 1996), and is extensively metabolized via both oxidative and conjugative pathways (Hucker et al, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Cyclobenzaprine pharmacokinetics are linear for doses from 2.5 to 10 mg despite the slight deviations from linearity observed at the 5 mg dose (Winchell et al, 2002). Like other tricyclic antidepressants, cyclobenzaprine is also prescribed off-label as a sleep-aid.…”
Section: Introductionmentioning
confidence: 99%